2018
DOI: 10.1136/bcr-2017-222756
|View full text |Cite
|
Sign up to set email alerts
|

Case of chest pain in a young man

Abstract: A young man with a history of smoking presented with acute-onset chest pain after lifting weights. He also noticed a change in his voice, tightness in his neck and difficulty breathing. A chest radiograph showed soft tissue emphysema in the neck. A CT scan of the chest revealed moderate amount of pneumomediastinum tracking into the neck and down to the diaphragm. He was haemodynamically stable and had no hypoxia or dysphagia. He was monitored for 48 hours and discharged home after resolution of his symptoms. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Primary pulmonary diseases can have atypical presentations [1,2]. Lung cancer is the leading cause of cancer related mortality worldwide [[3], [4], [5]].…”
Section: Discussionmentioning
confidence: 99%
“…Primary pulmonary diseases can have atypical presentations [1,2]. Lung cancer is the leading cause of cancer related mortality worldwide [[3], [4], [5]].…”
Section: Discussionmentioning
confidence: 99%
“…Primary pulmonary diseases can have atypical presentations [ 1 , 2 ]. Lung cancer is the leading cause of cancer related mortality worldwide [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer related mortality worldwide [1][2][3][4][5]. The data from the US National Lung Screening Trial (NLST) showed annual low-dose computed tomography (LDCT) for lung cancer screening in the high-risk population reduced lung cancer mortality by 20% compared with a chest x-ray (CXR) [6].…”
Section: Opinionmentioning
confidence: 99%